Wall Teichoic Acids Facilitate the Release of Toxins from the Surface of Staphylococcus aureus - Tarcisio Brignoli; Edward Douglas; Seána Duggan; Olayemi Grace Fagunloye; Rajan Adhikari; M. Javad Aman; Ruth C. Massey (Microbiology Spectrum, 2022)
ABSTRACT A major feature of the pathogenicity of Staphylococcus aureus is its ability to secrete cytolytic toxins. This process involves the translocation of the toxins from the cytoplasm through the bacterial membrane and the cell wall to the external environment. The process of their movement through the membrane is relatively well defined, involving both general and toxin-specific secretory systems. Movement of the toxins through the cell wall was considered to involve the passive diffusion of the proteins through the porous cell wall structures; however, recent work suggests that this is more complex, and here we demonstrate a role for the wall teichoic acids (WTA) in this process. Utilizing a genome-wide association approach, we identified a polymorphism in the locus encoding the WTA biosynthetic machinery as associated with the cytolytic activity of the bacteria. We verified this association using an isogenic mutant set and found that WTA are required for the release of several cytolytic toxins from the bacterial cells. We show that this effect is mediated by a change in the electrostatic charge across the cell envelope that results from the loss of WTA. As a major target for the development of novel therapeutics, it is important that we fully understand the entire process of cytolytic toxin production and release. These findings open up a new aspect to the process of toxin release by a major human pathogen while also demonstrating that clinical isolates can utilize WTA production to vary their cytotoxicity, thereby altering their pathogenic capabilities. IMPORTANCE The production and release of cytolytic toxins is a critical aspect for the pathogenicity of many bacterial pathogens. In this study, we demonstrate a role for wall teichoic acids, molecules that are anchored to the peptidoglycan of the bacterial cell wall, in the release of toxins from S. aureus cells into the extracellular environment. Our findings suggest that this effect is mediated by a gradient of electrostatic charge which the presence of the negatively charged WTA molecules create across the cell envelope. This work brings an entirely new aspect to our understanding of the cytotoxicity of S. aureus and demonstrates a further means by which this major human pathogen can adapt its pathogenic capabilities.